A study on predicting cases that would benefit from proton beam therapy in primary liver tumors of less than or equal to 5 cm based on the estimated incidence of hepatic toxicity. (July 2022) - Uchinami, Yusuke; Katoh, Norio; Suzuki, Ryusuke; Kanehira, Takahiro; Tamura, Masaya; Takao, Seishin; Matsuura, Taeko; Miyamoto, Naoki; Fujita, Yoshihiro; Koizumi, Fuki; Taguchi, Hiroshi; Yasuda, Koichi; et al.
Highlights: An advantage of PBT is reducing the liver receiving low doses of radiation. The factors predicting the benefit in PBT are different among NTCP models. The tumor size, number, and location are useful in estimating the benefits of PBT. Abstract: Background: For small primary liver tumors, favorable outcomes have been reported with both of proton beam therapy (PBT) and X-ray therapy (XRT). However, no clear criteria have been proposed in the cases for which and when of PBT or XRT has to be used. The aim of this study is to investigate cases that would benefit from PBT based on the predicted rate of hepatic toxicity. Materials and methods: Eligible patients were those who underwent PBT for primary liver tumors with a maximum diameter of ≤ 5 cm and Child-Pugh grade A (n = 40). To compare the PBT-plan, the treatment plan using volumetric modulated arc therapy was generated as the XRT-plan. The rate of predicted hepatic toxicity was estimated using five normal tissue complication probability (NTCP) models with three different endpoints. The differences in NTCP values (ΔNTCP) were calculated to determine the relative advantage of PBT. Factors predicting benefits of PBT were analyzed by logistic regression analysis. Results: From the dose-volume histogram comparisons, an advantage of PBT was found in sparing of the normal liver receiving low doses. The factors predicting the benefit of PBT differed depending on the selected NTCP model. From the five models, the total tumor diameter (sum of the target tumors), location (hepatic hilum vs other), and number of tumors (1 vs 2) were significant factors. Conclusions: From the radiation-related hepatic toxicity, factors were identified to predict benefits of PBT in primary liver tumors with Child-Pugh grade A, with the maximum tumor diameter of ≤ 5 cm.